The Reasons of the Reluctance of Secondary School Teachers in the Province of Houtat Bani Tamim Of Leadership Positions in The Schools of The Province - Al- Tamimi, Nourah Mohammed (Journal of Educational and Psychological Sciences, 2019)
This research aimed to recognize the reasons made the high school teachers (female) in Houtat Bani Tamim province abstains from the leadership's positions at the institutions that they are working in. And to achieve the goals of the research the descriptive analytical approach was used, while the study tool was an electronic questionnaire distributed among a random simple sample which consisted of (93) secondary teachers. The study revealed that the arithmetic averages of the responses of the study sample on the axis of reasons for abstention from leadership positions ranged between (2.62) and (3.94) with a general average of (3.46) (3.45) and (4.31) with a general average of (3.92). The results of the study on the analysis of mono- variance showed that there were no statistically significant differences due to differences in academic qualifications and years of experience. This reflects the agreement of the sample members of the secondary school teachers on the reasons of abstention of leadership positions.
Keywords: reasons; reluctance; secondary teachers; leadership positions